MicroRNA in Implant Dentistry: From Basic Science to Clinical Application - Menini, Maria; Dellepiane, Elena; Pera, Francesco; Izzotti, Alberto; Baldi, Domenico; Delucchi, Francesca; Bagnasco, Francesco; Pesce, Paolo (MicroRNA, 2021)
Specific microRNA (miRNA) expression profiles have been reported to be predictive of specific clinical outcomes of dental implants and might be used as biomarkers in implant dentistry with diagnostic and prognostic purposes. The aim of the present narrative review was to summarize current knowledge regarding the use of miRNAs in implant dentistry. The authors attempted to identify all available evidence on the topic and critically appraise it in order to lay the foundation for the development of further research oriented towards the clinical application of miRNAs in implant dentistry.
Keywords: osteogenesis